Strategies in forward osmosis membrane substrate fabrication and modification: A review - Suzaimi, N.D. (MDPI AG, 2020)
Forward osmosis (FO) has been recognized as the preferred alternative membrane-based separation technology for conventional water treatment technologies due to its high energy efficiency and promising separation performances. FO has been widely explored in the fields of wastewater treatment, desalination, food industry and bio-products, and energy generation. The substrate of the typically used FO thin film composite membranes serves as a support for selective layer formation and can significantly affect the structural and physicochemical properties of the resultant selective layer. This signifies the importance of substrate exploration to fine-tune proper fabrication and modification in obtaining optimized substrate structure with regards to thickness, tortuosity, and porosity on the two sides. The ultimate goal of substrate modification is to obtain a thin and highly selective membrane with enhanced hydrophilicity, antifouling propensity, as well as long duration stability. This review focuses on the various strategies used for FO membrane substrate fabrication and modification. An overview of FO membranes is first presented. The extant strategies applied in FO membrane substrate fabrications and modifications in addition to efforts made to mitigate membrane fouling are extensively reviewed. Lastly, the future perspective regarding the strategies on different FO substrate layers in water treatment are highlighted. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.